Penerapan Algoritma A*Pathfinding dalam Pencarian Solusi Game Peanut Labirin dendgan Macromedia Flash - Hernika Ari Wibowo Didik Nugroho Wawan Laksito (STMIK Sinar Nusantara, 2012)
Branch of computer science in the field of artificial intelligence is often used to handle problems in a computer game, one of which is to find the two closest points that are often found in the maze game. In the world of computing, the algorithm is so much that can be used to find two pairs of points contained in the labyrinth area. One of the search algorithms that can be used is the A * pathfinding algorithm.This algorithm is one type of search algorithms that have information that is used to perform the search process. Algorithms * A is also known as an algorithm that efficiently and will provide optimal results.Here is used the Manhattan distance heuristic function type. From this test we will be able to see how the algorithm * to find the shortest path from the problem of maze maps created using macromedia flash and actionscript as a programming language.The success of the solution obtained using algorithm A * in solving the maze could not be separated from the use of the heuristic function in it. Keywords: Algorithm A *, heuristics, Labyrinth.